Kinetic analysis, potentiation, and fatigue during vertical and horizontal plyometric training: An in-depth investigation into session volume - Watkins, C. M.; Gill, N. D.; McGuigan, M. R.; Maunder, E.; Spence, A.-J.; Downes, P.; Neville, J.; Storey, A. G. (International Journal of Sports Physiology and Performance, 2023)
Despite previous support for plyometric training, optimal dosing strategies remain unclear.